UTILIZING ARCHAEOLOGICAL TRACES IN SINGARAJA AS A SOURCE OF MULTICULTURAL EDUCATION IN BALI - Komang Ayu Suwindiatrini (Kalyanamitra: Journal of Archaeological Resource Management, 2026)
Bali is known as the island of a thousand temples, but is it true that only Hinduism has grown and developed there? In fact, various relics of different religions can be found, especially in North Bali. In the era of the kingdom, North Bali once had a renowned harbor. There was a strong connection between the harbor, various activities, and encounters among people of diverse ethnicities, religions, and nations. This article focuses on the distribution of archaeological remains closely related to religion in Singaraja. Singaraja, the capital of the Kingdom of Buleleng, later became an afdeling and eventually the capital of the Sunda Kecil. Implicitly, the writing of this article also obtains results from existing archaeological traces and provides an identity to Singaraja as an multicultural city, that is not only rich in culture but also rich in elements of various religions which can be used as an educational resource.